The Case for Intervening in Bankers’ Pay - THANASSOULIS, JOHN (Journal of Finance, 2012)
ABSTRACT This paper studies the default risk of banks generated by investment and remuneration pressures. Competing banks prefer to pay their banking staff in bonuses and not in fixed wages as risk sharing on the remuneration bill is valuable. Competition for bankers generates a negative externality, driving up market levels of banker remuneration and hence rival banks’ default risk. Optimal financial regulation involves an appropriately structured limit on the proportion of the balance sheet used for bonuses. However, stringent bonus caps are value destroying, default risk enhancing, and suboptimal for regulators who control only a small number of banks.